Preliminary Failure Frequency Analysis of Receiving Bins in Retention Bunkers Operated in Underground Copper Ore Mines - Mateusz Szczerbakowicz; Natalia Suchorab; Robert Król (Applied Sciences, 2021)
Ore retention bunkers and receiving bins are important for continuous operation of transport system in a mine. Although the designs of the bins used in the KGHM PM S.A. mines have undergone modifications, their operating principle has remained unchanged since their initial commissioning. Their operation entails many problems, which are caused by the durability and functionality of the entire structure. Preventive actions and research into directions for possible modernizations require the type of damage and its reasons to be identified in the first place. This article presents an evaluation of the documented types of damage and an analysis of the repair works performed for the entire population of the receiving bins operated in one mine. The comparative evaluation of the bin failure rate is here proposed to be performed with the use of a number-based failure indicator and of a mass indicator. The key problem identified in the research was the wear and tear on steel elements due to abrasive processes. The linings of the bin elements were observed to undergo intensive abrasive wear. This abrasive wear of the analyzed bin elements is influenced by a combination of factors, the most important of which include variable physical and mechanical properties of the copper ore.